1986
DOI: 10.1002/zaac.19865400912
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for stability of oxidation states derived from photo‐electron spectra and inductive quantum chemistry

Abstract: The 315 oxidation states in non‐metallic, non‐catenated compounds are arranged according to their Kossel number of electrons K in 81 isoelectronic series. The profound differences between the four categories (the 4f, the 5f and the d groups, and the other elements) are analyzed and compared with ionization energies I of loosely bound electrons obtained from photo‐electron spectra, and their slope (dI/dZ). It seems difficult, but not impossible, still to prepare a few new oxidation states. The examples argon(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Likely candidates for ArF + salts have been the subject of speculation in the literature. Jørgensen suggested that [ArF] 2 [BeF 4 ] and [ArF][BF 4 ] might be stable while Frenking et al ruled out the latter salt and laid claim to [ArF][AuF 6 ] and [ArF][SbF 6 ] as being the more likely. Liebman and Allen, in a theoretical investigation, further proposed that ArF + might be “sufficiently stable to allow the probable isolation of [ArF + ][PtF 6 − ]”.…”
Section: Resultsmentioning
confidence: 99%
“…Likely candidates for ArF + salts have been the subject of speculation in the literature. Jørgensen suggested that [ArF] 2 [BeF 4 ] and [ArF][BF 4 ] might be stable while Frenking et al ruled out the latter salt and laid claim to [ArF][AuF 6 ] and [ArF][SbF 6 ] as being the more likely. Liebman and Allen, in a theoretical investigation, further proposed that ArF + might be “sufficiently stable to allow the probable isolation of [ArF + ][PtF 6 − ]”.…”
Section: Resultsmentioning
confidence: 99%
“…While the early 3d metals can readily form complexes in which the oxidation-state of the metal center is equal to the corresponding group number, it is recognized that high-oxidation-state 3d metal species are, in general, less stable than their 4d and 5d congeners. The situation can be discerned from the known highest oxidation states of late 3d metals, which are lower than the corresponding group numbers and also lower than those of their heavier congeners . For example, the heavier group 8 metals Ru­(VIII) and Os­(VIII) can form binary oxides of the form MO 4 , whereas FeO 4 is unknown and Fe­(VI), as in [FeO 4 ] 2– , is the highest oxidation state observed for Fe. , For the group 9 metals, while Ir­(IX) and Rh­(VI) species are known, , Co­(V), as in [Co­(1-norbornyl) 4 ]­[BF 4 ], , represents the highest oxidation state of this element.…”
Section: Challenges In the Stabilization Of High-oxidation-state 3d M...mentioning
confidence: 99%
“…The discovery of a short-lived +3 oxidation state of Hg in 1976, generated through electrochemical reduction [3], led to the search of its +4-oxidation state, which is expected to be more stable than the +3-oxidation state, because it has the same electronic configuration (5d 8 ) as the very stable Au 3+ cation [4]. Fifteen years after it was theoretically predicted [5][6], HgF 4 was synthesized under cryogenic conditions in rare gas matrices in 2007 [7].…”
mentioning
confidence: 99%